Mempersiapkan Warga Belajar STIT Raden Wijaya Mojokerto dalam Era Disruptions dengan Motto Toward Excellence As Integrated Education untuk Mengatasi Isu Kebangkrutan Perguruan Tinggi Secara Umum - Mohammad Badru Tamam (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The internet and its ability to provide faster and more extensive ways to access content are the main drivers of disruption in this story. This allows the aggregation and sorting of content and the dissemination of content to groups of people larger than is possible through previous forms of distribution. The researcher formulated a study on how to prepare the learning citizens of STIT Raden Wijaya Mojokerto in the era of disruptions with the motto toward excellence as integrated education ?. This research is